Efektivitas Storytelling Edukatif Terhadap Meningkatkan Pengetahuan Dan Kesadaran Anak Dalam Pola Makan Sehat - Nanda Verika; Indra Tri Astuti; Herry Susanto (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Childhood nutritional literacy is an important determinant of long-term health behavior, particularly in shaping healthy eating awareness during early school age development. This study aimed to examine the effectiveness of educational storytelling intervention in improving knowledge and awareness of healthy eating patterns among elementary school children using a pre-experimental one group pretest-posttest design. The study was conducted at SDN Sambirejo 02 Semarang City involving lower grade students selected through purposive sampling. Data were collected using a picture-based knowledge questionnaire and structured observation of eating awareness behavior, which had previously been tested for validity and reliability. Statistical analysis using paired sample t-test showed significant improvement in both knowledge and awareness scores after storytelling intervention with p-value < 0.001. The results indicate that narrative-based health education can enhance cognitive understanding and emotional engagement of children in learning nutrition concepts. Storytelling intervention provides an effective and child-friendly communication approach for promoting healthy dietary behavior in primary school settings